IDENTITY FROM AN IBN KHALDUNIAN PERSPECTIVE. THE SEARCH FOR THE CONCEPT OF IDENTITY WITHIN IBN KHALDUN’S MUQADDIMAH - Dorbane Hafidha; Boularaf Redhouane; Zelmat Ghania (International Journal of Innovative Technologies in Social Science, 2025)
The attempt to understand certain social concepts requires tracing them back to early stages of human thought. Returning to the fundamentals always clarifies the path these concepts have taken through their interaction with spatial, temporal, and epistemological contexts until reaching their contemporary form—such as the concept of identity. When speaking of sociology, Ibn Khaldun’s Muqaddimah stands as the foundational pillar of this science and the earliest systematic reflection on it. In it, he included his ideas about the phenomena and systems related to human society and civilization, and the resulting social, political, cultural, historical, and geographical issues—the core subjects of the science he founded. This research paper thus seeks to explore the concept of identity within Ibn Khaldun’s Muqaddimah, while also attempting to interpret it through sociological and even anthropological perspectives on identity. The study’s main findings indicate that the notion of identity appears in the Muqaddimah both as a term and as a social meaning expressing various forms of belonging and affiliation.